2020
DOI: 10.3233/ies-202106
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of a low-cost portable force platform

Abstract: BACKGROUND: A small, portable, inexpensive FP is a helpful test instrument in many strength and conditioning settings. OBJECTIVE: The purpose of this study was to assess the reliability and validity of a portable FP. METHODS: The FP was assessed statically for linearity and regionality using known weights and known weight placements across nine regions. Dynamic assessment was conducted by placing the FP on a laboratory-grade one-dimensional FP and performing static jumps, countermovement, and drop jumps with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Currently, vertical GRF can be measured in-field using AI [ 49 , 50 ], commercially available instrumented insoles [ 51 ], and one-dimensional force platforms [ 52 ]. This study demonstrated that using only vertical GRF resulted in significantly larger estimates of ACL loading ( Figure 2 , mean differences ranging from 89.1 to 253.8 N) compared to 3D GRF, irrespective of the neural model employed.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, vertical GRF can be measured in-field using AI [ 49 , 50 ], commercially available instrumented insoles [ 51 ], and one-dimensional force platforms [ 52 ]. This study demonstrated that using only vertical GRF resulted in significantly larger estimates of ACL loading ( Figure 2 , mean differences ranging from 89.1 to 253.8 N) compared to 3D GRF, irrespective of the neural model employed.…”
Section: Discussionmentioning
confidence: 99%
“…They can measure the value sampled in time of the force components applied to them according to the three axes. By processing these values, proper software can compute several parameters useful for functional assessment [55]. In particular, the main parameters investigated were the vertical force, the impulse force, the peak of force, the rate of force development, the acceleration, the velocity, the power, and the displacement position change [56].…”
Section: Dynamic Assessment Of Movement Performancementioning
confidence: 99%